Optimizing The Use of the Madurese Language in The Development of Religion Tourism at Syaikhona Kholil, BangkalanOptimizing The Use of the Madurese Language in The Development of Religion Tourism at Syaikhona Kholil, Bangkalan - Tiara Putri Sulung Rosetio; Zulkhaeriyah zulkhaeriyah (Journal of Social, Culture, and Language, 2025)
There is a lot of potential of Syaikhona Kholil, a religious tourism in Bangkalan in attracting both domestic and foreign tourists. By providing a unique cultural appeal and promoting local identity, speaking Madurese might improve tourism (Sukardi, 2022). However, despite having a large vocabulary, Madurese is still underused in this regard. Through local language and cultural exchange, this research seeks to maximize the use of Madurese in religious tourism at Syaikhona Kholil. This strategy encourages the preservation of Madurese culture while increasing visitor participation (Purnama, 2023). To evaluate the influence of language on visitor experience, the study included stakeholder interviews, site surveys, and visitor surveys. The main objectives of this study are to identify the extent to which Madurese is used in the development of religious tourism at Syaikhona Kholil, assess the impact of its use on the tourist experience, and develop optimal strategies to increase the use of Madurese in the tourism sector. Findings are expected to significantly contribute to the enhancement of religious tourism in Bangkalan, especially through language and cultural preservation.